Drone deployed sensors: a tool for multiparametric near-vent measurements of volcanic explosions - Markus Schmid; Ulrich Kueppers; Johannes Huber; Donald B. Dingwell (Volcanica, 2023)
Observations and measurements on active volcanoes are commonly conducted at a distance considered safe from the inherent dangers linked to volcanic explosions. This reduction in proximity adds a degree of uncertainty to the interpretation of monitoring data due to enhanced signal path effects. Here, we describe custom-built, drone-deployable sensor platforms designed to acquire data at high proximity to volcanic vents. They are equipped with an environmental sensor capable of measuring temperature, relative humidity and barometric pressure, a microphone (6 Hz–20 kHz) to reconstruct the acoustic pressure, and an electrical resonant circuit to detect electrical signals in the 500 kHz frequency band. Communication and data transfer is achieved through a radio link between the sensor platform and the base station. Our sensor platforms may be employed in the collection of data of near-vent characteristics of volcanic explosions, observations that are essential for quantifying and understanding the driving forces underlying volcanic explosions.